Role for Mitochondrial Oxidants as Regulators of Cellular Metabolism - Nemoto, Shino (American Society for Microbiology, 2000)
Leakage of mitochondrial oxidants contributes to a variety of harmful conditions ranging from neurodegenerative diseases to cellular senescence. We describe here, however, a physiological and heretofore unrecognized role for mitochondrial oxidant release. Mitochondrial metabolism of pyruvate is demonstrated to activate the c-Jun N-terminal kinase (JNK). This metabolite-induced rise in cytosolic JNK1 activity is shown to be triggered by increased release of mitochondrial H(2)O(2). We further demonstrate that in turn, the redox-dependent activation of JNK1 feeds back and inhibits the activity of the metabolic enzymes glycogen synthase kinase 3β and glycogen synthase. As such, these results demonstrate a novel metabolic regulatory pathway activated by mitochondrial oxidants. In addition, they suggest that although chronic oxidant production may have deleterious effects, mitochondrial oxidants can also function acutely as signaling molecules to provide communication between the mitochondria and the cytosol.